PENERAPAN COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN PEMAHAMAN DAN KETERAMPILAN MAHASISWA (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The objectives of this study are: (1) to improve students’ understanding in Accounting Computer subject mahasiswa pada mata kuliah Komputer Akuntansi, (2) to improve students’ skills in Accounting Computer subject. The subject of this research is accounting students of education program that take accounting computer subject. This research is class action research consists of 3 cycles. The given action in the first cycle according to the result of beginning reflection. In every cycle consists of 4 stages that are planning, actuating, observation, and reflection. This research reached standardized indicator that 70% students have minimum score that was 71 (B). It showed that the application of cooperative learning jigsaw type can improve the students’ ability in a computer accounting subject. Key Words : Cooperative Learning, Jigsaw, the students’ understanding, creativity